Petrological and Geochronological Peculiarities of Novoukrainka Massif Rocks and Age Problem of Uranium Mineralization of the Kirovograd Megablock of the Ukrainian Shield - Cuney, M.; Shcherbak, M.Р.; Emetz, A.V.; Petrychenko, K.V.; Sinelu, S. (Мінералогічний журнал, 2008)
Basing on the new and published data of isotopic dating, the ages of the rock complexes of the Novoukrainka granite massif (the Ukrainian Shield) and uranium mineralization in albitites with the complexes of the host rocks were compared. A sequence of the geologic events in the Ingul megablock of the Ukrainian Shield is marked: formation of the Kirovograd (2025–2060 mln. y. ago) and Novoukrainka (2025–2040 mln. y. ago) magmatic complexes — formation of the uranium deposits (~ 1800 mln. y. ago, but the age should be precised) — Korsun-Novomyrgorod magmatic complex (1730–1760 mln. y. ago). The Novoukrainka massif is presented by differentiated magma of the magmatic melt originated from the upper crust material.